Our multi-storied bodies: in practitioner-centred conversations - Poh Lin Lee; Helena Rose (Murmurations)
We will share five fragments of a collaborative exchange where multi-storied bodies practices are brought to practitioner-centred conversations. Our written dialogue woven throughout will illustrate how these practices create opportunities to disrupt professional binaries such as personal/professional, thought/feeling, and individual/collective. We will show how each turn in our exchange was taken and how this has shaped the practice. The story of this collaboration is at its heart, and we will therefore begin there.